Caught in the middle: a thematic analysis of the experiences of Korean-Canadian caregiver-employees in the greater Toronto and Hamilton area - Joonsoo S. Lyeo; Allison Williams (BMC, 2021)
Abstract Background The objective of this study was to investigate the experiences of caregiver-employees (CEs) from the Korean-Canadian community in the Greater Toronto and Hamilton Area. Methods Nine participants were recruited and invited to partake in data collection, which consisted of the completion of a sociodemographic questionnaire as well as a qualitative, semi-structured interview. The interview transcripts were thematically analyzed. Result The thematic analysis revealed four primary themes, each of which had three sub-themes. The four primary themes are:: (i) tensions, (ii) adaptations to the dual role of being a CE, (iii) coping mechanisms, and (iv) desired changes to the status quo. Conclusion The result of this study suggest that Korean-Canadian CEs, as a consequence of their position at the convergence of Korean and Western cultural values, would be best supported through the provision of culturally sensitive supports and greater workplace accommodation.